The effect of the use of proton pump inhibitors, serotonin uptake inhibitors, antihypertensive, and anti‐inflammatory drugs on clinical outcomes of functional dental implants: A retrospective study. Issue 8 (30th June 2022) - Corbella, Stefano; Morandi, Paolo; Alberti, Alice; Morandi, Benedetta; Francetti, Luca
Abstract: Objective: The present retrospective study investigated the effect of chronic intake of proton pump inhibitors, selective serotonin uptake inhibitors, anti‐inflammatory, and antihypertensive drugs on the survival of dental implants and on the occurrence of peri‐implantitis. Materials and methods: Survival analyses for implant failure and peri‐implantitis were performed patient level for each drug subcategory and for risk factors. The HR for each drug was calculated with adjusted models as compared with a control group made of subjects not assuming the specific drug. Multilevel logistic regression was used to explore the influence of implant‐level and patient‐level variables on the outcomes. Results: A total of 270 subjects receiving 1118 dental implants were included, with a mean follow‐up time of 5.19 ± 4.22 years. After 10 years, the survival rate was 86.9% (patient level), and according to survival analysis, 61.3% of subjects were free from peri‐implantitis. The use of anti‐inflammatory medicines produced a significant effect ( p  = .04) on peri‐implantitis as compared to subjects not using the drug, with a 2.7‐year drop in the mean survival time. The HR was slightly above the level of significance in a semiadjusted model ( p  = .058). The multilevel analysis found a significant effect on the entire sample and not when considering only subjects with implants with more than 1‐year follow‐up. Conclusions: We found a possible relationship between anti‐inflammatory drug use and the occurrence of peri‐implantitis in the examined cohort of patients, and no correlation for the other drugs.